Effect of hope therapy on depression, anxiety, and stress among the patients undergoing hemodialysis - Meisam Rahimipour; Nahid Shahgholian; Mohsen Yazdani (Wolters Kluwer Medknow Publications, 2015)
Background: Renal failure is a major public health problem in the world. These patients experience high levels of psychological tension, anxiety, and depression, which leads to their lowered quality of life, increased health care costs, and early mortality. Due to medication side effects in these patients, non-medicational methods are more in demand now. This study aimed to investigate the effect of hope therapy on depression, anxiety, and stress among the patients undergoing hemodialysis. Materials and Methods: This is a clinical trial. Fifty patients undergoing hemodialysis were selected. Patients were assigned to two groups of hope therapy and placebo. Intervention of hope therapy was administered for 60-90 min during dialysis sessions once a week for eight sessions. In the placebo group, non-specific intervention was administered with the same number of sessions. Depression, Anxiety, and Stress scale (DASS)-21 questionnaire was completed at the end of the last session and 4 weeks later. Data were analyzed by paired t-test, repeated measures analysis of variance (ANOVA), and least significant difference (LSD) post hoc test through SPSS 18. Results: There was a significant difference in mean scores of depression, anxiety, and stress in hope therapy group before, immediately after, and 1 month after intervention (P < 0.05), while there was no significant difference in mean scores of depression, anxiety, and stress before and immediately after intervention in the placebo group. Changes in mean scores of depression, anxiety, and stress were significantly higher in hope therapy group compared to placebo (P < 0.05). Conclusions: The obtained results showed that hope therapy is effective on reduction of depression, anxiety, and stress.